2008
DOI: 10.1016/j.heares.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and temporal cues for speech recognition: Implications for auditory prostheses

Abstract: Features of stimulation important for speech recognition in people with normal hearing and in people using implanted auditory prostheses include spectral information represented by place of stimulation along the tonotopic axis and temporal information represented in low-frequency envelopes of the signal. The relative contributions of these features to speech recognition and their interactions have been studied using vocoder-like simulations of cochlear implant speech processors presented to listeners with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
69
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 77 publications
2
69
1
Order By: Relevance
“…Xu and Pfingst measured both consonant and vowel recognition as a function of the number of channels (1 to 16) and upper limit of modulation frequency (1 to 512 Hz) [4]. The knee points of vowel recognition for different numbers of channels are all below about 4 Hz.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xu and Pfingst measured both consonant and vowel recognition as a function of the number of channels (1 to 16) and upper limit of modulation frequency (1 to 512 Hz) [4]. The knee points of vowel recognition for different numbers of channels are all below about 4 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…The signal in each band can be regarded as a temporal amplitude envelope with a carrier (temporal fine structure). The temporal envelope of speech has been proved to be an important cue for speech perception from the studies using noise-vocoded speech (NVS) [1][2][3][4]. NVS is generated by replacing the carriers with band-limited noise, so the spectral cue is reduced dramatically and the temporal cue is preserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is surprising, because listeners with normal hearing did not show much importance for low frequency channels. This increased reliance on low frequency channels may be due to the fact that cochlear implants have relatively poor ability to convey place of excitation cues, but are better at conveying temporal envelope cues (Xu and Pfingst, 2008). Experiments in listeners with normal hearing with transposed tones, sounds where low rate modulation is applied to a high frequency carrier, demonstrated that correct (i.e., low frequency) place of excitation is necessary to perceive the fundamental frequency of low rate modulation (Oxenham et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For more difficult speech with multiple talkers, and for speech in noise, more channels are needed; long-electrode CI users continue to improve their reiss@ohsu.edu speech recognition up to 7-8 channels (Friesen et al, 2001). In contrast, NH subjects listening to a simulation of longelectrode processed speech improve their speech recognition up to 22 or more channels and so achieve higher speech recognition scores than CI subjects (Friesen et al, 2001;Xu and Pfingst, 2008). One proposed explanation for the limited ability of CI users to improve speech recognition with more than 7-8 stimulation channels out of up to 22 available intracochlear electrodes is that current spread and the resulting channel interactions limit the speech recognition benefit to every third electrode.…”
Section: Introductionmentioning
confidence: 99%